A text message program as a booster to in-person brief interventions for mandated college students to prevent weekend binge drinking. Issue 6 (17th August 2016) - Suffoletto, Brian; Merrill, Jennifer E.; Chung, Tammy; Kristan, Jeffrey; Vanek, Marian; Clark, Duncan B.
ABSTRACT: Objective : To evaluate a text message (SMS) program as a booster to an in-person alcohol intervention with mandated college students.Participants : Undergraduates ( N = 224; 46% female) who violated an on-campus alcohol policy over a 2-semester period in 2014.Methods : The SMS program sent drinking-related queries each Thursday and Sunday and provided tailored feedback for 6 weeks. Response rates to SMS drinking-related queries and the associations between weekend drinking plans, drinking-limit goal commitment, and alcohol consumption were examined. Gender differences were explored.Results : Ninety percent of SMS queries were completed. Weekend binge drinking decreased over 6 weeks, and drinking-limit goal commitment was associated with less alcohol consumption. Compared with women, men had greater reductions in alcohol consumption when they committed to a drinking-limit goal.Conclusions : Preliminary evidence suggests that an SMS program could be useful as a booster for helping mandated students reduce weekend binge drinking.